2020
DOI: 10.1177/0194599819897265
|View full text |Cite
|
Sign up to set email alerts
|

Global Burden of Head and Neck Cancer: Economic Consequences, Health, and the Role of Surgery

Abstract: Objective We aimed to describe the mortality burden and macroeconomic effects of head and neck cancer as well as delineate the role of surgical workforce in improving head and neck cancer outcomes. Study Design Statistical and economic analysis. Setting Research group. Subjects and Methods We conducted a statistical analysis on data from the World Development Indicators and the 2016 Global Burden of Disease study to describe the relationship between surgical workforce and global head and neck cancer mortality-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 43 publications
1
113
0
1
Order By: Relevance
“…For those countries that do have good data recording, there is a lack of data centralization and limited access for those individuals interested in studying GBD or other surgical trends. 1,2,7,8 How to Interpret and Use the Unseen…”
Section: Lack Of Data Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…For those countries that do have good data recording, there is a lack of data centralization and limited access for those individuals interested in studying GBD or other surgical trends. 1,2,7,8 How to Interpret and Use the Unseen…”
Section: Lack Of Data Reportingmentioning
confidence: 99%
“…The pursuit to define the global burden of disease (GBD) has been an expanding field of research for surgeons, especially since the publication of the Lancet Commission on Global Surgery in 2015. 1 By clearly describing the surgical deficits and challenges facing low- and middle-income countries (LMICs), the commission suggested that expanded efforts should be taken to better understand the surgical GBD. In doing so, along with a myriad of other important research endeavors, the global medical community could enter an era of global medicine with a new approach.…”
mentioning
confidence: 99%
“…2 Developing countries also account for 67% of head and neck cancers and 82% of head and neck cancer-related deaths. 3 Cancer of the head and neck is therefore primarily a disease of the developing world. However, the way head and neck cancers are investigated and treated in developed versus developing countries is increasingly divergent because of technological advances and financial and infrastructural differences.…”
Section: Commentarymentioning
confidence: 99%
“…[2][3][4] This is a significant issue, given the high mortality associated with head and neck cancer. [5] Within the craniofacial skeleton, titanium dental implants have been implemented for more than 50 years due to the ability of surface-optimised titanium to osseointegrate. [6,7] More recently, larger load-bearing titanium prostheses have been used as zygomatic implants for bone-poor maxillae and oncological defects [8] and temporomandibular joint prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2‐4 ] This is a significant issue, given the high mortality associated with head and neck cancer. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%